Tatak Pilipino [episode no. 61] [videorecording]. ([Quezon City ABS-CBN], 1992)
A unique display of Pilipino ways and style.
Illegitimate children (15 min.) -- Aphrodisiacs (10 min.) -- Pinoy lovers (15 min.) -- Love story of Rolando/Ella Tinio (10 min.).
Keywords: Tinio, Rolando; Illegitimate children -- Philippines; Aphrodisiacs; Filipinos; Love stories; Home economics; Sociology